1988
DOI: 10.1111/j.1365-2621.1988.tb09277.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐E. coli lmmunoglobulin Y Isolated from Egg Yolk of Immunized Chickens as a Potential Food Ingredient

Abstract: Active immunoglobulin (IgY) was isolated from egg yolk of chickens immunized with formalin-treated E. coli. The antibody activity was measured by enzyme-linked immunosorbent assay using E. coli lipopolysaccharide as an antigen. The anti-E. coli IgY aggregated the bacterial cells and inhibited their growth in rjit~a. IgY was rclativcly heat-stable without loss in antibody activity by pasteurization. IgY was stable at pH above 4, but was more susccptiblc to pepsin than bovine IgC, while apprcciablc activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
1
4

Year Published

1992
1992
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 25 publications
10
79
1
4
Order By: Relevance
“…2). These results are coincident with those reported by Shimizu et al 15 ) Therefore, it is noted that trypsin and chymotrypsin do not completely degrade the active site of the IgY. The difference in the digestion pattern of IgY found between the two enzymes could be due to the difference in their specificities on the IgY H-chain, although more evidence and clarification are necessary.…”
Section: -10)supporting
confidence: 78%
See 2 more Smart Citations
“…2). These results are coincident with those reported by Shimizu et al 15 ) Therefore, it is noted that trypsin and chymotrypsin do not completely degrade the active site of the IgY. The difference in the digestion pattern of IgY found between the two enzymes could be due to the difference in their specificities on the IgY H-chain, although more evidence and clarification are necessary.…”
Section: -10)supporting
confidence: 78%
“…The activity measured by neutralization titer of anti-HRV IgY was completely lost by peptic digestion at pH 4.0 in the same digestive conditions (enzyme/substrate == 1/20, 37°C, 4 h) as those of Shimizu et al 15 ) (data not shown). However, a considerable extent of neutralization titer of anti-HRV IgY (630/0 of the initial value) remained on incubation with pepsin (E/S = 1/200, 37°C, 4 h) at pH 4.0, although the titer decreased to almost zero at pH 2.0 (Table I).…”
Section: -10)mentioning
confidence: 52%
See 1 more Smart Citation
“…However, there are reports in the literature that suggest that the IgY F ab fragments maintain their ability to bind antigen, even after exposure to pepsin and trypsin and at pH 4.0 (Shimizu et al, 1988;Carlander et al, 2000;. Therefore, there may be a percentage of the yolk containing IgY digested with only a limited portion still being active post-digestion.…”
Section: Prophylaxis Trialmentioning
confidence: 93%
“…Anticorpos IgG de galinhas imunizadas são transportados eficientemente e acumulados na gema do ovo (Shimizu et al, 1988 O aumento da ingestão de matéria seca devido ao uso de anticorpos na alimentação de bovinos confinados tem sido relatado por diversos autores Gill et al, 2000;Shu et al, 2000). Animais recebendo PAP e MON apresentaram similares (P > 0,05) GPD, CMS e CA.…”
Section: Anticorpos Policlonaisunclassified